Synthesis of Some New N’-[5’-(N10-Phenothiazinomethyl)-1’,3’,4’-thiadiazol-2’- yl] N-aryl guanidine hydrochlorides with Possible Antithyroid Activity - Raj Singh, Gir; C. Mehra, S. (Asian Journal of Chemistry, 2010)
Several new N´-[5´-(N10-phenothiazinomethyl)-1´,3´,4´-thiadia-zol-2´-yl] N-aryl guanidine hydrochlorides (I) have been synthesized by the reaction of 2-amino-5-(N10- phenothiazinomethyl)-1,3,4-thiadiazole with different aryl cyanamides. All these synthesized aryl guanidines have been screened for their antithyroid activity. The compounds were characterised by elemental analysis, IR and NMR spectra.